2012
DOI: 10.1017/s0950268812000210
|View full text |Cite
|
Sign up to set email alerts
|

Comparative seroepidemiology of diphtheria in six European countries and Israel

Abstract: Serological surveys for diphtheria were conducted in six European countries including Czech Republic, Hungary, Ireland, Latvia, Luxembourg, Slovakia and one country outside Europe, Israel. For each country, a nationally representative population sample was collected across the entire age range and was tested for antibodies to diphtheria toxin. Although each national laboratory used its preferred assay, the results were all standardized to those of the in vitro neutralization test and expressed in international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
(44 reference statements)
4
20
0
Order By: Relevance
“…But in our studies <50% children in age 0–2 years old had protective level of antibodies whereas Edmunds et al [16] showed that >90% of 1 year olds were seropositive (various tests were used, such as ELISA, DELFIA, ToBI and the Vero cell neutralization test). A low proportion of seropositive children was also identified in the Czech Republic (using the Vero cell neutralization test) [14]. Our results together with results obtained for Czech population support the opinion of Chironna et al [17], that basic immunization without booster doses may result in unsatisfactory protection among children.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…But in our studies <50% children in age 0–2 years old had protective level of antibodies whereas Edmunds et al [16] showed that >90% of 1 year olds were seropositive (various tests were used, such as ELISA, DELFIA, ToBI and the Vero cell neutralization test). A low proportion of seropositive children was also identified in the Czech Republic (using the Vero cell neutralization test) [14]. Our results together with results obtained for Czech population support the opinion of Chironna et al [17], that basic immunization without booster doses may result in unsatisfactory protection among children.…”
Section: Discussionsupporting
confidence: 85%
“…In all European countries where diphtheria seroprevalence studies were conducted, including Poland, the level of antibodies to diphtheria toxin decreases significantly in persons above 40 years old [14,16,24-29]. The most drastic decrease was observed in Poland (this study), Spain and Ireland, reaching > 67% of seronegative individuals [14,25].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…From 1996 to 2003 annual seroepidemiological studies were carried out in Latvia. Studies in European countries have indicated that immunity levels below the protective level (> 0.1 IU) increased with age of adults [24]. On average in Latvia, for 23% of adults the immunity level was lower than protective and for 30% of adults it was protective.…”
Section: Discussionmentioning
confidence: 99%
“…To monitor the effectiveness of control programmes and inform policy Reviewing vaccination history on all cases through enhanced surveillance is a valuable means of monitoring the effectiveness of the vaccine. Seroprevalence studies can also be used to assess whether or not the vaccination programme is sufficiently protective, as well as monitoring the degree of waning immunity and the duration of protection (Edmunds et al 2000;Di Giovine et al 2012). A high case fatality ratio may indicate problems with late diagnosis, case management, or the availability or quality of antibiotics and/or antitoxin.…”
Section: Objectives Of Diphtheria Surveillancementioning
confidence: 99%